Essentials of operative cardiac surgery - Punjabi, Prakash P. (Springer, 2014)
This book will aid surgeons in mastering the essential skills necessary in the ever expanding field of cardiac surgery. As well as presenting basic surgical principles, emphasis throughout the book has been placed on providing essential tips to make every cardiac surgical operation easy, reproducible and safe to perform, and tricks to enable surgeons to manage the difficult situations they are likely to encounter and prevent serious complications. Essentials of Operative Cardiac Surgery is an indispensable text for trainees and established consultants in adult cardiac surgery.